2023
DOI: 10.1111/1752-1688.13094
|View full text |Cite
|
Sign up to set email alerts
|

Change of stream network connectivity under polder‐type flood control measure

Abstract: Polder is usually used for flood control in the river delta area. With the rapid development of urbanization, the dikes or pumps cut the original stream network system, and the stream network connectivity (SNC) and the river system pattern have changed. The dikes or pumps generally force up the river's water level, and regional flood formation mechanisms and processes have changed. In order to quantitatively describe the characteristics of polder‐type flood control measure (PFCM) and the change law of SNC, fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Numerous scholars and experts have delved into exploring these hydraulic features. Gao et al [9] established a hydrological and hydrodynamic model by combining the MIKE11 model and the hydrological modeling system to explore the changes in a river network's connectivity with flood control measures. The results showed that dike-type flood control measures have a negative impact on the connectivity of the river network, and attention should be paid to the number and opening and closing status of water pumps.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous scholars and experts have delved into exploring these hydraulic features. Gao et al [9] established a hydrological and hydrodynamic model by combining the MIKE11 model and the hydrological modeling system to explore the changes in a river network's connectivity with flood control measures. The results showed that dike-type flood control measures have a negative impact on the connectivity of the river network, and attention should be paid to the number and opening and closing status of water pumps.…”
Section: Introductionmentioning
confidence: 99%